2021
DOI: 10.3390/cancers13164071
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Aryl Hydrocarbon Receptor Favors K-RasG12D-Driven Non-Small Cell Lung Cancer

Abstract: Non-small cell lung adenocarcinoma (NSCLC) bearing K-RasG12D mutations is one of the most prevalent types of lung cancer worldwide. Aryl hydrocarbon receptor (AHR) expression varies in human lung tumors and has been associated with either increased or reduced lung metastasis. In the mouse, Ahr also adjusts lung regeneration upon injury by limiting the expansion of resident stem cells. Here, we show that the loss of Ahr enhances K-RasG12D-driven NSCLC in mice through the amplification of stem cell subpopulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, these undifferentiated cells exhibited their highest expansion at the early stages of regeneration, suggesting that Ahr is needed to control stemness at the initial “priming phases” of liver recovery. This hypothesis is further supported by previous studies indicating that Ahr is a determining factor in controlling cell undifferentiation in diverse repairing processes including those regenerating the liver 22 and the lung 56 and even during NSCLC induced by the KRas-G12D human oncogene in an Ahr deficient background 44 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, these undifferentiated cells exhibited their highest expansion at the early stages of regeneration, suggesting that Ahr is needed to control stemness at the initial “priming phases” of liver recovery. This hypothesis is further supported by previous studies indicating that Ahr is a determining factor in controlling cell undifferentiation in diverse repairing processes including those regenerating the liver 22 and the lung 56 and even during NSCLC induced by the KRas-G12D human oncogene in an Ahr deficient background 44 .…”
Section: Discussionsupporting
confidence: 76%
“…We have shown that Ahr is required to adjust liver regeneration after acute toxic injury 22 and we and others have reported that Ahr serves to reduce hepatocarcinogenesis burden caused by postnatal exposure to diethylnetrosamine in mice 22,41 . Moreover, previous work also suggest that the higher regenerative potential and increased susceptibility to carcinogenesis of Ahr-null mice could be due to their more undifferentiated and pluripotent phenotype in different organs including liver 21,22,30,[42][43][44][45] . In this study, we have investigated potential mechanisms through which Ahr adjusts liver regeneration in response to a massive tissue removal resembling that used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Further insights in multi-step lung carcinogenesis were provided by Miura et al, showing that exogenous HER2 expression in iPSC-derived human lung organoids induced the formation of tumor-like structures and a transcriptional profile similar to LUAD with HER2 amplification [ 70 ]. Nacarino-Palma and colleagues investigated the role of Aryl Hydrocarbon Receptor (AHR) in murine lung organoids, showing that AHR loss cooperates with oncogenic KRAS to promote organoid stemness and self-renewal [ 71 ]. Sàndor and coworkers used LUAD organoids to identify a Wnt-producing microniche composed by both cancer cells and fibroblasts, which was able to influence cancer cell proliferation and extracellular vesicle release.…”
Section: Preclinical Applications Of Lung Cancer Organoidsmentioning
confidence: 99%
“…The lack of the receptor in AHR-null mice increases the stem population in repairing lung and liver ( Morales-Hernández et al, 2017 ; Moreno-Marín et al, 2017 ); while AHR activation in hematopoietic stem/progenitor cells affects cellular proliferation, trafficking and migration ( Sakai et al, 2003 ; Casado et al, 2011 ; Singh et al, 2011 ). In the KrasG12D-AHR–/– mouse model, lungs contain increased numbers of cells expressing markers for both progenitor clara and alveolar type II cells, and also have elevated numbers of cells positive for pluripotent stem cells markers ( Nacarino-Palma et al, 2021b ).…”
Section: Involvement Of Aryl Hydrocarbon Receptor In Tissue Homeostas...mentioning
confidence: 99%
“…The use of experimental models, in which AHR expression has been interfered with, shows a more undifferentiated phenotype and ultimately a more pluripotent basal state, which has consequently, among others yet to be identified, a more effective regenerative capacity ( Morales-Hernández et al, 2017 ; Moreno-Marín et al, 2017 ). Such enhanced regenerative capacity also appears when major lung stem cells responsible for regeneration and repair after injury, including type-II alveolar cells and Clara cells, are amplified in K-Ras G12D/+ ; AHR −/− NSCLC lesions ( Nacarino-Palma et al, 2021b ). This links to the opportunity offered by cellular reprogramming in the research of the rejuvenation process ( Mahmoudi and Brunet, 2012 ; Mahmoudi et al, 2019 ), highlighting its relevance in the use of cell reprogramming in iPSC-based regenerative therapies.…”
Section: Cell Reprogramming: a New Path For Aryl Hydrocarbon Receptormentioning
confidence: 99%